Role of School Nurses in Preventing Digital Addiction and Promoting Health Among School-Age Adolescents - Marwa Shafiek Saleh (NASN School Nurse, 2026)
Excessive digital technology use among adolescents has become an increasing public health concern, with growing evidence linking problematic smartphone, internet, gaming, and social media use to sleep disturbances, anxiety, depression, reduced academic performance, cyberbullying exposure, and sedentary behaviors. While many school-based efforts have traditionally focused on preventing digital addiction, there is increasing recognition of the need to adopt a broader digital wellness promotion approach that encourages balanced, safe, and healthy technology use. School nurses, through their daily interactions with students and their role in school health promotion, are uniquely positioned to support adolescent digital health. This article briefly discusses the major health risks associated with excessive digital engagement among adolescents and highlights the expanding role of school nurses in promoting digital wellness through assessment, education, counseling, collaboration, and advocacy.